Reduction of Advanced Breast Cancer Stages at Subsequent Participation in Mammography Screening - Weigel, S.; Heindel, W.; Heidrich, J.; Heidinger, O.; Hense, H. W. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2016)
Purpose: The decline in advanced breast cancer stages is presumably the most relevant surrogate parameter in mammography screening. It represents the last step in the causal cascade that is expected to affect breast cancer-related mortality. To assess the effectiveness of population-based screening, we analyzed the 2-year incidence rates of advanced breast cancers between women participating in the initial and in the first subsequent round.Materials and Methods: The study included data from 19 563 initial and 18 034 subsequent examinations of one digital screening unit (2008 – 2010). Data on tumor stages, detected by screening or within the following interval of two years (2-year incidence), were provided by the epidemiological cancer registry. Rates of all and combined UICC stages 2, 3 and 4 (advanced stages) were reported for a two-year period. Proportions were tested for significance by using chi-square tests (p < 0.001).Results: The 2-year incidence rate of all stages was significantly lower in participants in subsequent screening than in initial screening (0.85 vs. 1.29 per 100 women (%); p < 0.0001). A significantly lower 2-year incidence of advanced stages was observed for subsequent screening compared to initial screening (0.26 % vs. 0.48 %; p = 0.0007). Among women aged 50 to 59 years, the incidence of advanced stages was less clearly different (0.21 % vs. 0.35 %; p = 0.07) than in women aged 60 to 69 years (0.31 % vs. 0.70 %; p = 0.0008).Conclusion: During the change from prevalent to incident phase mammography screening, a program impact is seen by a lower 2-year incidence of advanced breast cancers within subsequent compared to initial participants, predominately in women aged 60 to 69 years.Key Points:• The incidence of advanced tumor stages represents the most relevant surrogate parameter for screening effectiveness.• For the first time the 2-year incidence of advanced breast cancer stages after subsequent mammography screening was analyzed.• We observed a significant effect of screening on the 2-year incidence of advanced stages, predominately in the age group 60 to 69 years.Citation Format:• Weigel S, Heindel W, Heidrich J et al. Reduction of Advanced Breast Cancer Stages at Subsequent Participation in Mammography Screening. Fortschr Röntgenstr 2016; 188: 33 – 37
Keywords: breast cancer; population-based screening; digital mammography; interval cancer; effectiveness